2021
DOI: 10.1007/jhep11(2021)092
|View full text |Cite
|
Sign up to set email alerts
|

From the BTZ black hole to JT gravity: geometrizing the island

Abstract: We study the evaporation of two-dimensional black holes in JT gravity from a three-dimensional point of view. A partial dimensional reduction of AdS3 in Poincaré coordinates leads to an extremal 2D black hole in JT gravity coupled to a ‘bath’: the holographic dual of the remainder of the 3D spacetime. Partially reducing the BTZ black hole gives us the finite temperature version. We compute the entropy of the radiation using geodesics in the three-dimensional spacetime. We then focus on the finite temperature c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
61
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(62 citation statements)
references
References 36 publications
1
61
0
Order By: Relevance
“…This nice feature of double holography naturally leads to a geometric perspective of the black hole formation and evaporation. Since this exciting development, a variety of very interesting models have explored different techniques to geometrize the island formulation [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]. In this article we focus on another distinct recent geometric construction proposed in [20].…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…This nice feature of double holography naturally leads to a geometric perspective of the black hole formation and evaporation. Since this exciting development, a variety of very interesting models have explored different techniques to geometrize the island formulation [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]. In this article we focus on another distinct recent geometric construction proposed in [20].…”
Section: Introductionmentioning
confidence: 99%
“…Since this exciting development, a variety of very interesting models have explored different techniques to geometrize the island formulation [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]. In this article we focus on another distinct recent geometric construction proposed in [20]. The authors in [20] motivated by [26], demonstrated that the evaporation of a two dimensional Jackiw-Teitelboim black hole could be modelled by a partial dimensional reduction of a three dimensional BTZ black hole.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations